2017
DOI: 10.1002/cbdv.201700077
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Antimicrobial Activity of Dehydrozingerone based Cyclopropyl Derivatives

Abstract: A small series of 1-acetyl-2-(4-alkoxy-3-methoxyphenyl)cyclopropanes was prepared, starting from dehydrozingerone (4-(4-hydroxy-3-methoxyphenyl)-3-buten-2-one) and its O-alkyl derivatives. Their microbiological activities toward some strains of bacteria and fungi were tested, as well as their in vitro cytotoxic activity against some cancer cell lines (HeLa, LS174 and A549). All synthesized compounds showed significant antimicrobial activity and expressed cytotoxic activity against tested carcinoma cell lines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…2,4,[9][10][11] However, the substitution in the aromatic ring of the compound with an aminomethyl group via Mannich reaction has not been reported yet. In this study, a series of five novel Mannich bases of DHZ (2a-e) was synthesized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,[9][10][11] However, the substitution in the aromatic ring of the compound with an aminomethyl group via Mannich reaction has not been reported yet. In this study, a series of five novel Mannich bases of DHZ (2a-e) was synthesized.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Various chemical modification of DHZ has been performed to exploit for diverse biological activities of DHZ derivatives, such as esterification or alkylation of OH phenolic group, replacement of OH with other substituents, substitution of the methoxy group, reduction of double bond, cyclization of α,β-unsaturated carbonyl, and substitution of hydrogen atom bound to the carbonyl α-carbon. 2,4,[9][10][11] Some Mannich bases of DHZ have been synthesized and reported to have better anti-inflammatory activity compared to DHZ and fairly good anti-inflammatory activity compared to indomethacin. However, the aminomethyl group was substituted at the carbonyl α-carbon of the compound.…”
Section: Introductionmentioning
confidence: 99%
“…Alkylation/ allylation of the phenol group of the vanillin was achieved by a standard procedure [8][9][10] using an alkyl/allyl halide to yield the corresponding phenoxy compounds 1(a-j). Starting from our previous results in dehydrozingerone derivatives transformation 11,12 we decided to prepare some dehydrozingerone analogues, with rigid cyclopropane ring fragment instead of methyl one, in reaction O-alkyl vanillines and methyl cyclopropyl ketone. On this way, chalcone like compounds 2(a-j), (E)-1-cyclopropyl-3-(4-alkoxy-3methoxyphenyl)prop-2-en-1-ones were synthesized.…”
Section: Synthesis Of N-acetyl and N-formyl Pyrazoline Derivatives Frmentioning
confidence: 99%
“…Previous research of antimicrobial activity led to different conclusions with most of the studies evidencing markedly lower antifungal activity, 7,26 although a study conducted in 2012 determined that palladium(II) complexes with a derivative of thiosalicylic acid as ligand showed significantly higher antifungal activity towards species from the Aspergillus genus (A. fumigatus, A. flavus and A. restrictus) than the positive control, fluconazole. 6 Garoufis et al explored the antifungal and antibacterial activity of Pd(II) complexes with various ligands (sulphur and nitrogen donor ligands, Schiff bases and ligands used as drugs), and found that they had promising antibacterial but weak antifungal activity.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Special attention is paid to the study of the antimicrobial activity of complex compounds with different metal ions. [4][5][6][7] The chemical behaviour in solution of structurally analogous Pt(II) and Pd(II) complexes is very similar. 8 Since the antitumor activity of certain Pd(II) complexes has been demonstrated, the idea arose to examine several structurally different Pd(II) complexes for their antimicrobial activity as well as their interaction with calf thymus DNA (CT-DNA).…”
Section: Introductionmentioning
confidence: 99%